Surface‐Driven Evolution of the Anomalous Hall Effect in Magnetic Topological Insulator MnBi2Te4 Thin Films (Adv. Funct. Mater. 28/2022). (11th July 2022) - Mazza, Alessandro R.; Lapano, Jason; MeyerIII, Harry M.; Nelson, Christopher T.; Smith, Tyler; Pai, Yun‐Yi; Noordhoek, Kyle; Lawrie, Benjamin J.; Charlton, Timothy R.; Moore, Robert G.; Ward, T. Zac; Du, Mao‐Hua; et al.
Abstract : Magnetic Topological Insulators Targeted modification of properties is crucial to engineer novel phenomena such as the quantum anomalous Hall effect. In article number 2202234, Gyula Eres, Matthew Brahlek, and co‐workers show that the anomalous Hall effect in the magnetic topological insulator MnBi2 Te4 is highly tunable, to the point of complete sign reversal, by modification of the top‐most layer via oxidation, which is linked to a subtle rebalancing of the global magnetic state.